ACCOUNTING FUNDAMENTALS AND THE VARIATION OF STOCK PRICE Factoring in the Investment Scalability - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
This study develops a new return model with respect to accounting fundamentals. The new return model is based on Chen and Zhang (2007). This study takes into account the investment scalability information. Specifically, this study splits the scale of firms operations into short-run and long-run investment scalabilities. We document that five accounting fundamentals explain the variation of annual stock return. The factors, comprised book value, earnings yield, short-run and long-run investment scalabilities, and growth opportunities, coassociate positively with stock price. The remaining factor, which is the pure interest rate, is negatively related to annual stock return. This study finds that inducing short-run and longrun investment scalabilities into the model could improve the degree of association. In other words, they have value relevance. Finally, this study suggests that basic trading strategies will improve if investors revert to the accounting fundamentals